The NMDA receptors - Hashimoto, Kenji (Receptors, 2017)
This volume provides a history of and an update on the functional status of the NMDA receptors. The NMDA receptors are essential for neuronal development, synaptic plasticity, learning, and cell survival. It covers molecular, cellular, anatomical, biochemical, and behavioral aspects, to highlight their distinctive regulatory properties, their functional significance, and their therapeutic potential in a number of diseases. A group of international experts discuss the development of NMDA receptors, their basic functions, and how they are implicated in a wide range of diseases including depression, psychosis, and pain.